2004
DOI: 10.1090/s0025-5718-04-01648-5
|View full text |Cite
|
Sign up to set email alerts
|

Recovering signals from inner products involving prolate spheroidals in the presence of jitter

Abstract: Abstract. The paper deals with recovering band-and energy-limited signals from a finite set of perturbed inner products involving the prolate spheroidal wavefunctions. The measurement noise (bounded by δ) and jitter meant as perturbation of the ends of the integration interval (bounded by γ) are considered. The upper and lower bounds on the radius of information are established. We show how the error of the best algorithms depends on γ and δ. We prove that jitter causes error of order Ω 3 2 γ, where [−Ω, Ω] is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The prolate spheroidal wave functions, originated from the context of separation of variables for the Helmholtz equation in spheroidal coordinates (see, e.g., [20,12]), have been extensively used for a variety of physical and engineering applications, such as wave scattering, signal processing, and antenna theory (see, for instance, [3,11,17]). Most notably, a series of papers by Slepian et al [25,19,26] and the recent works by Xiao and Rokhlin et al [33,32,24,22] have shown that the PSWFs are a natural and optimal apparatus for approximating bandlimited functions.…”
Section: Introductionmentioning
confidence: 99%
“…The prolate spheroidal wave functions, originated from the context of separation of variables for the Helmholtz equation in spheroidal coordinates (see, e.g., [20,12]), have been extensively used for a variety of physical and engineering applications, such as wave scattering, signal processing, and antenna theory (see, for instance, [3,11,17]). Most notably, a series of papers by Slepian et al [25,19,26] and the recent works by Xiao and Rokhlin et al [33,32,24,22] have shown that the PSWFs are a natural and optimal apparatus for approximating bandlimited functions.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Development of numerical methods using PSWFs as basis functions, e.g., spectral/ spectral-elements methods (see, e.g., [5,7,10,13,50,51,92,107]), and wavelets (see, e.g., [15,[88][89][90]).…”
Section: Introductionmentioning
confidence: 99%